Domestication of High-Copy Transposons Underlays the Wheat Small RNA Response to an Obligate Pathogen. (15th November 2019) - Poretti, Manuel; Praz, Coraline Rosalie; Meile, Lukas; Kälin, Carol; Schaefer, Luisa Katharina; Schläfli, Michael; Widrig, Victoria; Sanchez-Vallet, Andrea; Wicker, Thomas; Bourras, Salim
Abstract: Plant genomes have evolved several evolutionary mechanisms to tolerate and make use of transposable elements (TEs). Of these, transposon domestication into cis-regulatory and microRNA (miRNA) sequences is proposed to contribute to abiotic/biotic stress adaptation in plants. The wheat genome is derived at 85% from TEs, and contains thousands of miniature inverted-repeat transposable elements (MITEs), whose sequences are particularly prone for domestication into miRNA precursors. In this study, we investigate the contribution of TEs to the wheat small RNA immune response to the lineage-specific, obligate powdery mildew pathogen. We show that MITEs of the Mariner superfamily contribute the largest diversity of miRNAs to the wheat immune response. In particular, MITE precursors of miRNAs are wide-spread over the wheat genome, and highly conserved copies are found in the Lr34 and QPm.tut-4A mildew resistance loci. Our work suggests that transposon domestication is an important evolutionary force driving miRNA functional innovation in wheat immunity.